S100A8/A9 Molecular Complexes Promote Cancer Migration and Invasion via the p38 MAPK Pathway in Nasopharyngeal Carcinoma - Ning Xu; Bei-Bei Zhang; Xia-Ning Huang; Xiang Yi; Xue-Min Yan; Yan Cai; Qin He; Zi-Jian Han; Yuan-Jiao Huang; Wei Liu; Ai-Jun Jiao (Bioinorganic Chemistry and Applications)
Nasopharyngeal carcinoma (NPC) is one type of malignancy associated with migration and invasion through a currently unclear mechanism. We previously discovered S100A8/A9 levels were roughly elevated in the plasma of NPC patients as the promising biomarkers. However, their expressions and underlying functions in NPC tissues are still unknown. In the present study, we analyzed 49 NPC tissues and 20 chronic pharyngitis (CP) tissues. Immunohistochemical staining was performed in different tissues and analyzed by the Mann–Whitney U test statistically. Transwell migration and invasion experiments were further performed to determine S100A8/A9 effects on NPC. Our results showed that S100A8/A9 in NPC tissues were significantly higher than those in CP tissues, closely associated with NPC clinical stages. Intriguingly, exogenous S100A8/A9 protein stimulation could dramatically enhance NPC migration and invasion abilities. In addition, p38 MAPK pathway blockade could diminish the migration and invasion of NPC cells stimulated by S100A8/A9 proteins. The downstream tumor invasion and migration associated proteins (e.g., MMP7) were also elevated in NPC tissues, consistent with S100A8/A9 overexpression. Taken together, our present findings suggest that the secreted soluble inflammatory factors S100A8/A9 might promote cancer migration and invasion via the p38 MAPK signaling pathway along with invasion/migration associated proteins overexpression in the tumor microenvironment of NPC. This may shed light on the mechanism understanding of NPC prognosis and provide more novel clues for NPC diagnosis and therapy.